A Three-dimensionally Printed Acrylonitrile Butadiene Styrene Model for the Reduction of Nasomaxillary Fracture. Issue 10 (18th October 2021) - Ikebe, Shohei; Niimi, Yosuke; Hasegawa, Yuki; Kamei, Wataru; Hori, Keijiro; Masamune, Ken; Sakurai, Hiroyuki
Abstract : Summary: The successful reduction of a nasomaxillary fracture was performed using a three-dimensional printed model. A 16-year-old boy was struck in the left orbit by a baseball; subsequently, he was diagnosed with the nasal bone fracture at a hospital, and was referred to the authors' department. A left nasomaxillary fracture and nasal bone fracture were diagnosed by computed tomography. Standard triangulated language data for the mirror image of the frontal process of the right maxilla were obtained from digital imaging and communications in medicine data for preparing a three-dimensional printed acrylonitrile butadiene styrene model. On postinjury day 13, the frontal process fracture was reduced via transconjunctival and intraoral approaches. After the reduction of the fracture, an absorbable plate fitting to the shape of three-dimensional printed acrylonitrile butadiene styrene model was molded, and the maxillary frontal process and infraorbital rim were reduced and fixed with an absorbable plate and screws. Postoperative computed tomography demonstrated a favorable reduction. The intraoperative use of the 3D printed acrylonitrile butadiene styrene model was helpful in the nasomaxillary fracture reduction and fixation.